RESPONSE OF MEDITERRANEAN GRASSLAND SPECIES TO CHANGING RAINFALL. - Figueroa, M. E.; Davy, A. J. (Journal of Ecology, 1991)
Investigates the long-term changes in the composition of a species-rich Mediterranean grassland in south-western Spain. Determination of the frequency of every species of herbaceous vascular plants annually; Domination of winter annual vegetation; Correlations between the logit of the total annual frequency of each species and rainfall totals; Link between species abundance and rainfall.
Keywords: BOTANY; Grasslands; MEDITERRANEAN Coast (Spain); RAINFALL frequencies; SPAIN (citation)